Strategic plan for the Kababayen-an alang sa Teknolohiya nga Haum sa Kinaiyahan ug Kauswagan (KATAKUS) - Esguerra, Michael M. (School of Management, University of the Philippines Mindanao, 2010)
According to David (1997) strategic management can be defined as the art and science of formulating, implementing, and evaluating cross-functional decisions that enables an organization to achieve its objective.